Investigação do potencial biólogico de derivados e análogos do canabidiol. - Adna Rafaella Barbosa de Souza (2023)
Delta-9-tetrahydrocannabinol and cannabidiol (THC and CBD) are phytocannabinoids with great therapeutic potential. Present in Cannabis sativa, the former is recognized for its psychoactive effects, and the latter for its broad therapeutic effect. CBD is a potent anticonvulsant, antitumor, anti-inflammatory, and antinociceptive agent. However, it has low bioavailability after oral administration and is only available in the form of oily solutions. Planning CBD analogs is a possibility to overcome the limitations associated with the use of this substance. In this study, the aim was to investigate the antioxidant, antitumor, anti-inflammatory, and antinociceptive potential of eight derivatives and analogs of CBD. The evaluation of antioxidant activity was performed using three chemical methods (FRAP, DPPH, and ABTS). As a result, MPP_CBD and CBD_R104 stood out in ABTS and DPPH reduction tests. The antitumor profile was tested using three tumor cell lines: chronic myeloid leukemia (K-562), acute monocytic leukemia (THP-1), and human breast adenocarcinoma (MDA-MB-231), by determining the value of the 50% inhibitory concentration (IC50). Among the substances analyzed, MPP_CBD, CBD_R104, RAC6, and RAC6_Ab demonstrated IC50 values close to those of drugs used as positive controls. In vitro anti-inflammatory activity was determined by indirectly measuring nitric oxide (NO) levels, where all substances blocked NO production. Levels of interleukin 2 (IL-2), interleukin 4 (IL-4), interleukin 6 (IL-6), interleukin 10 (IL-10), Tumor Necrosis Factor (TNF), interferon-gamma (IFNy), and interleukin 17A (IL-17A) were evaluated, and RAC6 and RAC6_Ab were able to reduce IL-6 levels. Finally, RAC6 showed activity when administered intraperitoneally at a dose of 20 mg/kg, without interfering with the animals' motor activity, and the proposed mechanism demonstrated that its action depends on interaction with the CB1 receptor. Thus, the present study highlighted that planning substances analogous to CBD is promising in the search for more active molecules with better pharmacokinetic potential.